Intelligent Selection of Machining Parameters in Multipass Turnings Using Firefly Algorithm. (10th February 2014) - Belloufi, Abderrahim; Assas, Mekki; Rezgui, Imane
Abstract : Determination of optimal cutting parameters is one of the most important elements in any process planning of metal parts. In this paper, a new optimization technique, firefly algorithm, is used for determining the machining parameters in a multipass turning operation model. The objective considered is minimization of production cost under a set of machining constraints. The optimization is carried out using firefly algorithm. An application example is presented and solved to illustrate the effectiveness of the presented algorithm.